2006
DOI: 10.1080/09540120500162213
|View full text |Cite
|
Sign up to set email alerts
|

Results of the Expanded HIV Risk Factor Assessment Project (EHRAP)

Abstract: An objective of EHRAP was to evaluate the HIV risk factor information reported to CDC through routine surveillance. HIV/AIDS surveillance programmes used medical and ancillary records to determine if information on HIV risk factors can be found for surveillance. Surveillance staff from Mississippi, South Carolina, and Virginia collected data on risk factors for HIV infection on a sample of cases diagnosed during 1998 and 1999. Overall percent agreement and Cohen kappa statistics were calculated for initially r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
(6 reference statements)
1
5
0
Order By: Relevance
“…One advantage of the multiple imputation method is that it provides appropriate (unbiased or less biased) estimates not only for the overall risk factor distribution, but also for the risk factor distribution within each subpopulation group that can be characterized by variables included in the imputation model. These results for the major transmission categories (four for males and two for females) compare favorably with detailed reviews of the medical records of females in three states during the late 1990s 8 and interviews conducted with females during the mid-1990s. 21 The Enhanced HIV Risk Factor Assessment Project, a review of medical records in three states, concluded that compared with medical record reviews, for females, risk factor redistribution overestimated IDU and underestimated HRH contact; for males, it overestimated male-to-male sexual contact and IDU and underestimated HRH contact.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…One advantage of the multiple imputation method is that it provides appropriate (unbiased or less biased) estimates not only for the overall risk factor distribution, but also for the risk factor distribution within each subpopulation group that can be characterized by variables included in the imputation model. These results for the major transmission categories (four for males and two for females) compare favorably with detailed reviews of the medical records of females in three states during the late 1990s 8 and interviews conducted with females during the mid-1990s. 21 The Enhanced HIV Risk Factor Assessment Project, a review of medical records in three states, concluded that compared with medical record reviews, for females, risk factor redistribution overestimated IDU and underestimated HRH contact; for males, it overestimated male-to-male sexual contact and IDU and underestimated HRH contact.…”
Section: Discussionsupporting
confidence: 62%
“…21 The Enhanced HIV Risk Factor Assessment Project, a review of medical records in three states, concluded that compared with medical record reviews, for females, risk factor redistribution overestimated IDU and underestimated HRH contact; for males, it overestimated male-to-male sexual contact and IDU and underestimated HRH contact. 8 Given the increase in the proportion of HIV cases that have occurred in females, estimates from multiple imputation appear not only plausible but more realistic than risk factor redistribution, for which data from the past four to 10 years are used. No interviews or medical record reviews have been conducted recently enough to serve as a comparison with our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the extent to which such misclassifications occur may be systematically overestimated. 30 It is also possible that some patients have other sources of risk for HIV transmission (transfusion, hemophilia, perinatal). However, these modes of transmission are currently rare in the United States and may be less frequently encountered in a sexual health clinic than in other settings.…”
Section: Discussionmentioning
confidence: 99%
“…One project, Expanded HIV Risk Factor Assessment Project (EHRAP) was conducted in three states to assess the best sources of supplemental risk factor information for describing and classifying cases reported without an identified risk factor. 15 Data from Mississippi, South Carolina, and Virginia were collected from intensive retrospective medical record reviews on a sample of cases diagnosed during 1998 and 1999. At the conclusion of the project, 96% of all cases had an identified risk factor, an increase from 68% at initiation.…”
Section: Ascertaining Hiv Risk Factorsmentioning
confidence: 99%